Organogenesis and plant regeneration of arachis villosa benth. (leguminosae) through leaf culture - Fontana, María Laura (2009)
Fil: Fontana, María Laura. Universidad Nacional del Nordeste. Facultad de Ciencias Agrarias; Argentina.